2015
DOI: 10.1161/jaha.115.001952
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction Determines Stress‐Induced Cardiovascular and Immune Complications in Mice

Abstract: BackgroundClinical studies suggest that acute inflammation in patients with elevated heart rate (HR) increases morbidity and mortality. The SJL/J (SJL) inbred mouse strain is a unique genetic model that has higher HR and systemic and vascular inflammation compared with C3HeB/FeJ (C3HeB) mice. The goal of this study was to investigate the role of stress on cardiac and vascular complications between 2 strains.Methods and ResultsRadiotelemetry was used for continuous recordings of HR and blood pressure in mice. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…Moreover, it is standard to train mice so that they become accustomed to the investigator and total process; however, our results are similar to those obtained by others23, 24 in that no reduction in blood pressure or heart rate was seen as a result of repeated exposure to the technique. On the contrary, repeated restraint and tail‐cuff recording over 5 consecutive days has been used by others as a method to induce stress,23 in support of the concept that the restraint component of the assay is associated with hemodynamic stress. However, it is our observation that mice become familiar with both the handling and the process of tail‐cuff, which can facilitate the collection of data.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, it is standard to train mice so that they become accustomed to the investigator and total process; however, our results are similar to those obtained by others23, 24 in that no reduction in blood pressure or heart rate was seen as a result of repeated exposure to the technique. On the contrary, repeated restraint and tail‐cuff recording over 5 consecutive days has been used by others as a method to induce stress,23 in support of the concept that the restraint component of the assay is associated with hemodynamic stress. However, it is our observation that mice become familiar with both the handling and the process of tail‐cuff, which can facilitate the collection of data.…”
Section: Discussionsupporting
confidence: 90%
“…It is believed that the mice habituate to the tail‐cuff procedure following repeated exposure and there is a common practice to “train” mice before starting an experiment 10, 21, 22. However, there is evidence that this does not happen 23, 24. Moreover, the tail‐cuff technique has been used to model stress that was defined by measuring heart rate 23…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many laboratories including ours have validated tail-cuff BP measurements by radiotelemetry method. Our recent study in inbred mouse strains showed significant correlation between our tail-cuff training protocol and radiotelemetry measurements of systolic BP 39 . We are confident in our results collected by tail-cuff method because of BP levels reflected degree of arterial remodeling obtained by histology across mice after DOCA-salt.…”
Section: Discussionmentioning
confidence: 63%